Preventive effects of dentifrice containing 5000 ppm fluoride against dental erosion in situ - Ren, Yan-Fang; Liu, Xuejun; Fadel, Noura; Malmstrom, Hans; Barnes, Virginia; Xu, Tao (Journal of dentistry, 2011)
To evaluate the effectiveness of a dentifrice with 5000 ppm fluoride in preventing dental erosion by orange juice in situ in comparison to a control dentifrice with 1450 ppm fluoride. This was a double-blind and randomized clinical study with a cross-over design. Sixteen subjects wore an intra-oral appliance containing two enamel disks with an exposed surface of approximately 2 mm × 5 mm. Enamel disks in the study group were treated with a dentifrice with 5000 ppm fluoride and in the control group with 1450 ppm fluoride. The subjects rinsed with slurries of study dentifrices for one minute before immersing the enamel disks in 250 ml orange Juice four times in an 8-h period daily. The treatment procedure was repeated for three 5-day phases for each dentifrice. Enamel erosion was measured after each 5-day treatment phase using a focus-variation 3D scanning microscopy. Medians and inter-quartile ranges (IQR) of mean erosion depth were compared between the groups. The mean erosion depths of enamel varied greatly amongst the subjects. Enamel treated with 5000 ppm fluoride had less erosion (median 5.7 μm, IQR 4.5 μm) as compared to the control (median 12.6 μm, IQR 12.3 μm) after 15 days of fluoride treatment and erosive challenge cycles ( p < 0.05). Enamel treated with 5000 ppm fluoride had significantly improved resistance to erosion by orange juice. Periodic application of 5000 ppm fluoride may be beneficial in individuals at risk of acidic erosion associated with soft drink consumptions.